Pengaruh Kualitas Produk, Fitur Produk dan Harga terhadap Niat Beli Ulang Melalui Kepuasan Konsumen sebagai Variabel Intervening (Studi pada Konsumen Smartphone Xiaomi di Kota Semarang) - Ari Cahyo Wicaksono; Sendhang Nurseto (Universitas Diponegoro, 2019)
Xiaomi is one of the smartphone brand whose products are currently widely used by the Indonesian people, especially in the city of Semarang. But in the last two years 2016-2017 Xiaomi smartphone sales have decreased and not reached the predetermined sales target. The purpose of this study is to determine the effect of product quality, features product , price, and consumer satisfaction to repurchase intention. This type of research is explanatory research which aims to explain the relationship and influence between the dependent variables independently through hypothesis testing, with a sample of 100 respondents who have bought Xiaomi smartphones through purposive sampling technique, namely determining samples based on certain considerations that fit the criteria. The method of analysis used in this research was two steps regression analysis. The results showed that there are positive effect between product quality to consumer satisfaction, features product to consumer satisfaction and between price to consumer satisfaction. Based on the two steps regression analysis showed that product quality, features product and price has an effect of consumer satisfaction. Furthermore, consumer satisfaction has an effect to repurchase intention. Suggestions in this study are to make more quality products, and make product features that have different characteristics from other brands.